Between profit and morality. Evidence from Robinhood investors trades in sin stocks - Omicioli, Gianmarco (2023)
This paper aims to study the behavior of Robinhood investors in the “Triumvirate of Sin” sectors, meaning tobacco, alcohol and casinos. The analysis includes several factors such as companies’ fundamentals, market sentiment, Google Trends and analyst coverage. Although sin industries are often studied collectively due to their similarities, my model portrays a different scenario for the three businesses, which is closely tied to the severity of the pandemic. In particular, a boost in the number of traders per day comes with an increase in share price only for the tobacco and alcohol sectors, while gambling has been adversely affected by the shutdowns of casinos, leading to a drastic drop in earnings.